Association between the American heart association’s life’s essential 8 score and cognitive function: a cross-sectional NHANES study - Jiuyang Sun; Xinyu Tu; Shuwei Wang; Jie Wang; Jingxue Liang; Zhenguo Liu; Lu Song (BMC Geriatrics)
Abstract Background Dementia is difficult to early diagnosis while intervention in late stage has limited effectiveness. Our study aimed to explore the associations between a potential risk factor, Life’s Essential 8 (LE8), and cognitive performance informs of cognitive test score and subjective cognitive performance. Methods Data were obtained from NHANES 2011–2012 and 2013–2014. Cognitive test score was measured by summary Z-scores of three cognitive test. Subjective cognitive performance was defined by self-reported cognitive problem. Multivariable regression models and restricted cubic spline models were applied to evaluate the association between LE8 score and two cognitive performances. Subgroup analysis and ROC analysis were also conducted to compare the predictive abilities of LE8 on cognitive test score and subjective cognitive performance. Result 964 individuals were included in our multivariable regression model (adjusted for age, gender, race, family income, education and alcohol consumption). The LE8 score is positively associated with both cognitive test scores and subjective cognitive performance. The effect of LE8 score on both cognitive test score and subjective cognitive performance showed a trend of linearity. LE8 score and cognitive test score showed a J-shaped dose response relationship. ROC curve indicated that LE8 score predicted better on objective cognitive test score than subjective cognitive performance. Among all LE8 metrics, physical activity, nicotine exposure, blood lipids and blood glucose significantly associated with cognitive test score while only physical activity significantly associated with subjective cognitive performance. Subgroup analysis suggested that LE8 predicted subjective cognitive performance better in high-cognitive test score sub-population than in low-cognitive test score sub-population. Conclusions LE8 score had significant linear association with both cognitive test score and subjective cognitive performance. LE8 predicted cognitive test score better and the regression coefficient increase more significant as LE8 score increase than subjective cognitive performance. Clinical trial number Not applicable.